2005
DOI: 10.1177/0891988705277541
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Sexual Behaviors in Dementia

Abstract: Dementias are the most common type of neurodegenerative disorder. Behavioral disturbances are seen in more than 80% of patients suffering from these disorders. Although sexually inappropriate behaviors are not as common as some of the other behaviors seen in dementia, they can cause immense distress to all those who are affected. There are no randomized trials for the treatment of these behaviors, but the available data suggest efficacy for some commonly used treatment modalities. In this review, we systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 52 publications
0
87
0
3
Order By: Relevance
“…There should be a good balance between openness to the patients need for normal sexual expression while preventing uncontrolled sexual behaviour [12]. It is also critical to prepare students for uncontrolled sexual behaviour.…”
Section: Behavioural Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…There should be a good balance between openness to the patients need for normal sexual expression while preventing uncontrolled sexual behaviour [12]. It is also critical to prepare students for uncontrolled sexual behaviour.…”
Section: Behavioural Treatmentmentioning
confidence: 99%
“…In some reviews of the literature, three types were suggested, i.e. sex talk, sexual acts, and implied sexual acts [11][12][13]. Sex talk is regarded as the most common form and involves inappropriate language, that is not in line with the patient's premorbid personality.…”
Section: Uncontrolled Sexual Behaviourmentioning
confidence: 99%
See 3 more Smart Citations